Adaptive Reuse in Industrial Heritage: A Bibliometric Review (2004-2024) - Ayşegül Çeltekligil; Feride Pınar Arabacıoğlu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
The reuse of post-industrial sites, frequently associated with contemporary themes, represents a subject of considerable interest and study at both the architectural and urban scales. The preservation and adaptive reuse of industrial heritage act as a conduit between the past and the future, while also contributing to urban sustainability. This study analyses the existing literature on repurposed industrial heritage sites, exploring relevant themes, general trends, and current directions. This study investigates approaches, concepts, keywords, authors, documents, organisations, and references within this context. English-language articles indexed in the Web of Science database were examined using the PRISMA protocol. The data obtained from the literature review were visualised through bibliometric mapping using VOSviewer software. Quantitative data were cross-analysed with qualitative and in-depth research findings. The study identifies themes, current trends, and research gaps concerning the reuse of industrial heritage sites.